2014
DOI: 10.1371/journal.pmed.1001633
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth and Risk of Stillbirth: A Population-Based Case–Control Study

Abstract: Radek Bukowski and colleagues conducted a case control study in 59 US hospitals to determine the relationship between fetal growth and stillbirth, and find that both restrictive and excessive growth could play a role. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 37 publications
(78 reference statements)
8
129
1
2
Order By: Relevance
“…The increased risk of being LGA and high birth weight, however, is of clinical importance. It has been shown that children that are LGA have an increased risk for caesarian section, metabolic disturbances, stillbirth, trauma, distress and asphyxia at birth [42][43][44]. There are studies that suggest epigenetic causes for the increased risk of being LGA in the FET group based on ART in animals [45].…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of being LGA and high birth weight, however, is of clinical importance. It has been shown that children that are LGA have an increased risk for caesarian section, metabolic disturbances, stillbirth, trauma, distress and asphyxia at birth [42][43][44]. There are studies that suggest epigenetic causes for the increased risk of being LGA in the FET group based on ART in animals [45].…”
Section: Discussionmentioning
confidence: 99%
“…The LGA child has an increased risk for stillbirth, asphyxia, distress, trauma, caesarian section, and metabolic disturbances at birth [15][16][17]. Moreover, another concern in LGA neonates born after assisted reproductive techniques (ART) is the possible underlying epigenetic pathology, since certain rare Capsule Besides maternal BMI, FET is a significant independent LGA risk factor in IVF patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 However pregnancy complication or feto-placental pathology are the major cause of fetal death.The pregnancy complication commonly associated with IUFD as reported in literature are preeclampsia, antpartum haemorrhage (APH), oligohydramnios, intrauterine growth restriction (IUGR). 6,8,9 Helgadottier LB found 68% of the cases the major cause of fetal death was placental pathology(IUFD8). 10 Factors or determinants of antepartum or intrapartum fetal death are not similar.…”
mentioning
confidence: 99%